ANALISIS KOMPUTASIONAL APLIKASI SUN COMPASS DALAM PENENTUAN ARAH KIBLAT MUSLIM: Computational Analysis of Sun Compass Application in the Determination of Muslim Qibla Direction - Abdul Niri, Mohamaddin; Ahmad Zaki, Nurulhuda; Mohd Nor, Mohamad Luqman Hakim (Jurnal Fiqh, 2023)
Sun Compass is a smartphone app that was developed to determine the Muslim qibla direction around the world. The invention of the Sun Compass is said to be a solution to the inaccuracy problem in Qibla app due to its susceptibility to magnetic interference. Based on the calibration technique of the sun’s shadow and true north reference, the Sun Compass showed a high accuracy of the Qibla direction angle. Therefore, this study was conducted to check the Sun Compass’s accuracy by comparing the Qibla direction display with the Qibla shadow. Data collection was carried out through field observation and the collected data were analysed computationally and comparatively. The results of the study found that the Sun Compass application has a deviation value of less than 0.5° with a 99%-confidence level of 0.1015 and it is still below the limit of deviation from the direction of the qibla (had al-tahawwul ‘ani al-qiblah) which, in Malaysia, is allowed for not more than 3°. This study concludes that the application of Sun Compass in assisting Muslims to determine the direction of Qibla is more accurate empirically than other Qibla apps.